2016
DOI: 10.1177/1029864916650719
|View full text |Cite
|
Sign up to set email alerts
|

Why go to pop concerts? The motivations behind live music attendance

Abstract: Recent technological innovations have facilitated widespread illegal downloading of recorded music. While this points towards a decreased willingness to pay for music, the increase in the popularity of live music suggests otherwise. This is especially so when taking into account the rising cost of concert tickets, likely the result of reduced recorded music revenues. In the present study, a consideration of the unique motivations of why music fans decide on whether or not to attend live concerts is of interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 44 publications
3
105
0
7
Order By: Relevance
“…However, they warn that the relationship between familiarity and liking is not yet understood. North and Hargreaves (1995), for example, found a positive association between familiarity and liking, whereas Brown and Knox (2016) concluded that audiences seek novelty rather than familiarity, and Thompson (2007) found no relationship between familiarity and audience members' enjoyment of a classical concert.…”
Section: Review Of Literaturementioning
confidence: 98%
“…However, they warn that the relationship between familiarity and liking is not yet understood. North and Hargreaves (1995), for example, found a positive association between familiarity and liking, whereas Brown and Knox (2016) concluded that audiences seek novelty rather than familiarity, and Thompson (2007) found no relationship between familiarity and audience members' enjoyment of a classical concert.…”
Section: Review Of Literaturementioning
confidence: 98%
“…They have grown in number, size and attendance (Abreu-Novais & Arcodia, 2013). Music festival attendance and the popularity of live music have grown in the face of declining recorded music sales (Brown & Knox, 2016;Anderton, 2011). This trend has been driven by the internet and the same technology that has slowed recorded music sales (Stone, 2008).…”
Section: History and Developmentmentioning
confidence: 99%
“…Ea l e e t management research into motivations to attend music festivals, for example Crompton and MacKay (1997); Bowen & Daniels (2005), used social psychology theories of leisure researchers like those of to underpin their studies, but ultimately reduced their findings to broad generalised categories that offered few subjective insights. Moreover, current research like that of Brown and Knox (2016) indicates that there has been little theoretical development around the motivations to attend music festivals in the last 20 years. This supports Abreu-Novais & Arcodia s ie that, while there are a number of studies in this area, the lack of methodological breadth means that this area of research is still under explored.…”
Section: Researching Experience and Music Festivalsmentioning
confidence: 99%
See 2 more Smart Citations